Hubungan Peran Tenaga Kesehatan, Orang Tua dan Teman Sebaya dengan Kejadian Kehamilan Dini pada Remaja di Wilayah Kerja Puskesmas Tanjung Puri Kalimantan Barat Tahun 2023 - Harahap, Tia Septianta; Nugraha, Susiana; Agustina, Santi (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2023)
Adolescence is a period of rapid growth and development, both physically and spiritually and intellectually. Teenage pregnancy can have an effect on women's reproductive and sexual health. The purpose of this study was to determine the relationship between the role of health workers, parents and peers with the incidence of early pregnancy in adolescents at the Tanjung Puri Health Center, West Kalimantan. The research method used a case control approach. The research site was at the Tanjung Puri Health Center in West Kalimantan and was conducted in May 2023. The independent variables are the role of health workers, the role of parents and the role of peers. The dependent variable is the incidence of early pregnancy. The sample was selected by purposive sampling with the number of respondents 1: 1, namely 65 adolescents experiencing early pregnancy and 65 adolescents not experiencing early pregnancy. The research instrument used a questionnaire, which was valid and reliable. Research analysis with univariate, chi square test and logistic regression using SPSS software. Research ethics based on certificate Number: 259/SK.KEPK/UNR/V/2023 from Respati University Indonesia.The results showed that there was an association between the role of health workers (p=0.048), parents (p=0.001) and peers (p=0.017) with the incidence of early pregnancy in adolescents. The results of the analysis showed that the most influential variable on the incidence of early pregnancy in adolescents was the role of parents (p=0,001 dan Exp (B) =5,112). The conclusion is that there is a relationship between the role of health workers, parents and peers with the incidence of early pregnancy in adolescents. Research advice is an input for the development of adolescent health quality, especially in terms of reducing the incidence of early pregnancy. Keywords : health workers, parents, peers, early pregnancy